Spatial query processing for skewed access patterns in non-uniform wireless data broadcast environments. (2017) - Shen, Jun-Hong; Jian, Ming-Shen
Location-based services (LBSs) via wireless data broadcast can provide a huge number of mobile clients for simultaneously accessing spatial data according to their current locations. Under non-uniform wireless data broadcast, more popular data appear more times than regular data, resulting in the decrease of the average client waiting time. In this paper, to efficiently support the processing of continuous window queries for LBSs, we propose a skewed spatial index considering clients' skewed access patterns in the non-uniform wireless broadcast environments. The index information considering the non-uniform broadcast is interleaved with the spatial objects on the wireless channel to support efficient access. From our experimental study, we have shown that our proposed method outperforms the multi-levelled air index scheme.